1998
DOI: 10.1046/j.1365-2850.1998.560431.x
|View full text |Cite
|
Sign up to set email alerts
|

Some reflections on cultural and social considerations in mental health nursing

Abstract: This article critiques the contribution of two main theoretical perspectives on mental health care and ethnicity, with particular reference to Asian women. It considers the work of those who highlight the impact of culture on the health and illness experience (Kleinman 1980, Rack 1982, Fernando 1989) and the work of authors who argue that the impact of broader socio‐economic structures must be considered (Donovan 1989, Pearson 1989, Ahmad 1993). It is posited that the emphasis on cultural difference results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Clearly, this would involve a fairly sensitive and sophisticated set of clinical skills-one that goes beyond the acknowledgement of cultural differences such as Asians-make-less-eye-contact types of messages that characterize and compromise cultural-competence training and skills in many settings (Bhui, Warfa, Edonya, McKenzie, & Bhugra, 2007). Simplifying in this manner maintains the structures of discrimination within communities and the mental health system (Burr & Chapman, 1998 …”
Section: Discussionmentioning
confidence: 99%
“…Clearly, this would involve a fairly sensitive and sophisticated set of clinical skills-one that goes beyond the acknowledgement of cultural differences such as Asians-make-less-eye-contact types of messages that characterize and compromise cultural-competence training and skills in many settings (Bhui, Warfa, Edonya, McKenzie, & Bhugra, 2007). Simplifying in this manner maintains the structures of discrimination within communities and the mental health system (Burr & Chapman, 1998 …”
Section: Discussionmentioning
confidence: 99%
“…; Sainola‐Rodriguez ; Wilson ). Nurses must understand the different views on the ‘normality’ of people who come from different cultures and should be able to comprehensively assess their mental health by taking into account cultural factors (Burr & Chapman ; Flaskerud & Kim ; Leininger ; Rashidi & Rajaram ).…”
Section: Introductionmentioning
confidence: 99%
“…Without transcultural knowledge, many psychiatric patients may be misunderstood, misdiagnosed or may receive insufficient treatment. Transcultural care is known to decrease conflicts and stressful situations, and it leads to an efficient and appropriate care experience (Burr & Chapman ; Flaskerud & Kim ; Leininger ; Rashidi & Rajaram ; Sandhu et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, many western health‐care interventions have been based on the concept that illness is culturally neutral and, therefore, interventions were applicable to all clients (Burr & Chapman 1998). Nevertheless, research has demonstrated that health and illness are culturally constructed experiences (Manderson 1990), which are manifested in different variations of illness (Balarajan & Soni Raleigh 1993).…”
Section: Introductionmentioning
confidence: 99%
“…According to Sheikh and Furnham (2000), the beliefs in more traditional cultures are deep‐rooted and more structured than in many western societies with religion playing a significant role in understanding the cause and treatment of illness. Burr and Chapman (1998; p. 434) claimed that ‘within each cultural system, illness, the response to illness and the method of treating illness, have different cultural and symbolic meanings’. However, knowledge of these cultural variations has failed to move health care out of its ethnocentric paradigm (Manderson & Mathews 1985).…”
Section: Introductionmentioning
confidence: 99%